2015
DOI: 10.1152/ajpcell.00323.2014
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide inhibits cell cycle activity of embryonic cardiac progenitor cells via its NPRA receptor signaling axis

Abstract: (NPRs), which can either activate guanylyl cyclase (NPRA and NPRB) or inhibit adenylyl cyclase (NPRC) to modulate intracellular cGMP or cAMP, respectively. During cardiac development, ANP serves as an early maker of differentiating atrial and ventricular chamber myocardium. As development proceeds, expression of ANP persists in the atria but declines in the ventricles. Currently, it is not known whether ANP is secreted or the ANP-NPR signaling system plays any active role in the developing ventricles. Thus the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…These studies notably reported activation of guanylyl cyclase-B by C-type natriuretic peptide or the inhibition of PDEs using 3-isobutyl-1-methylxanthine (IBMX) (45,46). Furthermore, during embryonic development, the regulation by the NPRA/ cGMP signaling pathway of the balance between proliferation and differentiation of cardiac progenitor cells is essential for cardiac growth (47). Therefore, the NPRA/cGMP signaling pathway appears to be a critical regulatory node for the effect of ANP on cardiac tissue homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…These studies notably reported activation of guanylyl cyclase-B by C-type natriuretic peptide or the inhibition of PDEs using 3-isobutyl-1-methylxanthine (IBMX) (45,46). Furthermore, during embryonic development, the regulation by the NPRA/ cGMP signaling pathway of the balance between proliferation and differentiation of cardiac progenitor cells is essential for cardiac growth (47). Therefore, the NPRA/cGMP signaling pathway appears to be a critical regulatory node for the effect of ANP on cardiac tissue homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…ANP and NPRA were involved in the fertilization process. Hotchkiss et al 35 found that NPRA was expressed on blastocysts and embryonic stem cells, and involved in maintaining embryonic stem cells self-renewal and pluripotency. Zhang et al 36 also reported that the binding of ANP and NPRA induced sperm acrosome reaction occurred, whereas the receptor antagonist could eliminate the effect of ANP.…”
mentioning
confidence: 99%
“…There are a myriad of experimental data describing the role of NPs and their receptors in cell signalling. Hotchkiss et al 79 aimed to evaluate the biological role of ANP signalling systems in embryonic ventricular myocardium. The authors identified local paracrine activity of ANP in the regulation of the balance between cardiac progenitor cell proliferation and differentiation through NPR‐A/cGMP‐mediated signalling pathways in the processes of developing mammalian ventricles 79 .…”
Section: Natriuretic Peptide Receptors Signalling In Heart Failurementioning
confidence: 99%
“…Hotchkiss et al 79 aimed to evaluate the biological role of ANP signalling systems in embryonic ventricular myocardium. The authors identified local paracrine activity of ANP in the regulation of the balance between cardiac progenitor cell proliferation and differentiation through NPR‐A/cGMP‐mediated signalling pathways in the processes of developing mammalian ventricles 79 . The cGMP molecule is able to target several downstream signalling pathways including protein kinase G (PKG), phosphodiesterase 2 (PDE2) and phosphodiesterase 3 (PDE3).…”
Section: Natriuretic Peptide Receptors Signalling In Heart Failurementioning
confidence: 99%